2021
DOI: 10.1111/jzo.12949
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns within an urban population of fire salamanders highlight the importance of conserving small habitat patches

Abstract: Movement is an ecological process that affects individual fitness and population dynamics of species. Understanding movement patterns is crucial for the effective conservation of amphibian populations isolated by urban development. Here, we conducted a capture-recapture study over 6 years in a population of the fire salamander (Salamandra salamandra) inhabiting a 7.3-ha patch of forest and disturbed land-use types in an urbanised catchment north-west of Budapest, Hungary. We investigated relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…In our study area, this could mean that larvae are almost completely washed out from a relatively short 485-m long stream segment; however, the presence of numerous pools likely prevented larval flushing from the stream. These larval dispersal distances also correspond fairly well with the observed distances moved by adult males, females and juvenile salamanders in the study area (Kiss et al 2022), and suggest that the population is largely restricted to the stream environment and adjoining terrestrial habitats. A similar finding was made for stream-adapted salamanders in another population within central Europe (Hendrix et al 2017).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In our study area, this could mean that larvae are almost completely washed out from a relatively short 485-m long stream segment; however, the presence of numerous pools likely prevented larval flushing from the stream. These larval dispersal distances also correspond fairly well with the observed distances moved by adult males, females and juvenile salamanders in the study area (Kiss et al 2022), and suggest that the population is largely restricted to the stream environment and adjoining terrestrial habitats. A similar finding was made for stream-adapted salamanders in another population within central Europe (Hendrix et al 2017).…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that the upper two thirds of the stream were preferred by females for larval deposition. Our parallel studies showed that the most favourable habitat conditions for adults were found in the same areas (Kiss et al 2021(Kiss et al , 2022. However, the distribution of larvae in stream sections may also be facilitated by the fact that females may visit several habitats when laying larvae as part of a risk-spreading strategy (Caspers et al 2015).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations